2021
DOI: 10.1155/2021/5594362
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria and Mold Spore Heat Resistance in Guava Juice and Its Control by pH and Sodium Benzoate

Abstract: Heat-resistant bacteria and molds can survive the pasteurization conditions used in high-acid fruit juices. The objective of this study was to evaluate the log reductions and thermal inactivation kinetics of spores of Bacillus subtilis bacteria and ascospores of Talaromyces flavus and Eupenicillium javanicum molds under influence of pH and sodium benzoate preservative. The spores were suspended in guava juice, processed at 90-100°C for B. subtilis and at 80-90°C for T. flavus and E. javanicum, and decimal redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the same study, these investigators obtained 3.15-23 log of A. niger conidia (depending on the water activity) also in Ringer solution after the 5 MPa dense CO2 with 60ºC process for 30 min. Our unpublished research showed P. variotii spore inactivation by 1.5 logs after 90ºC-10 min thermal processing alone [11], indicating no difference between the HPCDassisted and thermal processing of P. variotii in orange juice. Thus, the dense CO2-assisted thermal treatment in this study was concluded not enough to achieve significant inactivation.…”
Section: Th International Seminar On Fundamental and Application Of C...mentioning
confidence: 81%
“…In the same study, these investigators obtained 3.15-23 log of A. niger conidia (depending on the water activity) also in Ringer solution after the 5 MPa dense CO2 with 60ºC process for 30 min. Our unpublished research showed P. variotii spore inactivation by 1.5 logs after 90ºC-10 min thermal processing alone [11], indicating no difference between the HPCDassisted and thermal processing of P. variotii in orange juice. Thus, the dense CO2-assisted thermal treatment in this study was concluded not enough to achieve significant inactivation.…”
Section: Th International Seminar On Fundamental and Application Of C...mentioning
confidence: 81%